Legal Protection of Polar Environments in War - Kirchner, Stefan (2022)
Armed forces have long operated in polar environments and continue to play different roles in polar settings. In recent decades, polar law has emerged as a distinct discipline in international law, comprised of international Arctic law and the international law of Antarctica. In this text, the reader will be introduced to some particular aspects of the international legal regulation of polar spaces and the protection of the natural environment through international law in times of armed conflict. It is the aim of the text to identify connections between International Environmental Law (IEL) and International Humanitarian Law (IHL), and to answer the question if and how international legal norms that aim to protect the natural environment (especially the marine environment) in polar regions may be utilized to enhance compliance with IHL in case of an armed conflict in polar regions. To this end, the reader will be introduced to different types of threats to the natural environment experienced in polar regions and international treaties, documents created by international institutions, and academic writings will be analyzed. Special attention will be given to Polar Law and its two subsets, the international legal norms pertaining to Antarctica and the Southern Ocean and International Arctic Law (IAL) and to the existing governance structures for the Arctic, such as the Arctic Council (AC). The dramatic shifts in Arctic governance, away from cooperation between all eight Arctic states (A8) towards cooperation between the Arctic states minus Russia (A7 or West-Arctic) will be taken into account. It will be shown that the potential contribution to IHL by polar law is very limited and that some of the existing regulatory gaps can be closed but also that this possibility is largely theoretical as far as the risk of environmental pollution of the marine environment by warships is concerned.